Semiotic Views of Patriarchy in “The Hobbit” Movie by Peter Jackson - Khan, Dwiki Rahman; Rozelin, Diana; Lestari, Putri Ayu (Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2024)
This research aims to determine the elements of Patriarchism in the semiotic views found in the film The Hobbit written by Peter Jackson. Therefore, this research applies theories from Barthes (1968) and Leech and Onwuegbuzie (2008) regarding Semiotics and theories from Walby (1990) and Maine (1888) regarding Patriarchy as well as theories from Sanders (1860) and Peirce (1903) regarding Symbols , to make it easier for researchers to answer these problems. For research methods, this research uses the Qualitative Descriptive Research Method. For research data, researchers used the film The Hobbit written by Peter Jackson and other sources that were appropriate to the problem formulation. Research Results, (1) Researchers found the symbolism of Patriarchy from a semiotic perspective (2) found Patriarchy in non-verbal communication (3) found Patriarchy in verbal communication, Based on a basic analysis of Patriarchy, concrete evidence regarding patriarchy is realized and discussions of patriarchy are unique research because patriarchy is still alive in this modern era.